Building efficiency from bottom-up? Analysing global railway freight. (5th April 2010) - Hilmola, Olli-Pekka
Performance measurement systems have become popular, not only among industrial manufacturers, but also in the service sector. Due to increased global trade, importance of transportation sector has grown, not only for cost reasons, but for its environmental harm caused. In this research work we evaluate multi-stage data envelopment analysis (DEA) efficiency measurement model in global railway freight sector, where we assume a priori that operational performance leads into financial success through proposed model. However, empirical findings do not give any support for this, and it seems that operational inputs play central role in the performance concerning both output measurement levels.